A MAQASID-BASED WELFARE INDEX IN INDONESIA: AN EMPIRICAL INVESTIGATION - Suliswanto, Muhammad Sri Wahyudi; Mahyudi, Mohd; Barom, Mohd Nizam (Bank Indonesia, 2025)
Acknowledging the importance of having an alternative welfare measurement to the prevailing material-based conventional welfare index, this study formulates a maqasid-based welfare index that encapsulates the material, spiritual, and social needs of individuals and then calculates the index for all regions in Indonesia. Our proposed index is based on a comprehensive set of maqasid indicators and on appropriate weighting of each maqasid indicator to arrive at the index scores for all regions in the country. From the results, four provinces in Indonesia are at the high level of Maqasid-based welfare. They are Aceh, Nusa Tenggara Barat, Gorontalo, and Sulawesi Barat. Meanwhile, twenty-five provinces are at the medium range of welfare. The index we compute for each region should prove useful as it would allow policymakers to tailor welfare strategies to each province’s strong and weak areas of the maqasid al-shariah. ACKNOWLEDGEMENT Special thanks to Universitas Muhammadiyah Malang and International Islamic University Malaysia for their research support and valuable resources provided throughout this study.